2020
DOI: 10.1016/j.sjbs.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity from the continental shelf regions of the Eastern Arabian Sea: A metagenomic approach

Abstract: The marine microbiome is a complex and least-understood habitat, which play a significant role in global biogeochemical cycles. The present study reported the culture-independent assessment of microbial diversity from the Arabian Sea (AS) sediments (from Gujarat to Malabar; at 30 m depth) by using metagenome sequence analysis. Our results elucidated that bacterial communities in the Malabar coastal region are highly diverse than the Gujarat coast. Moreover, Statistical analysis (Spearman rank correlation) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Proteobacteria was the most dominant phyla in all the stations irrespective of the sampling period, with only marginal variations in the percentage of occurrence, with Betaproteobacteria, Alphaproteobacteria, and Gammaproteobacteria being the dominant classes. The dominance of Proteobacteria was in concurrence with reports from other tropical estuaries (Bouvier and del Giorgio 2002;Ghosh and Bhadury 2019;Ortmann and Santos 2016;Eswaran and Khandeparker 2019) and also from coastal waters of India (Sachithanandam et al 2020, Parvathi et al 2019. High abundance of Betaproteobacteria and Alphaproteobacteria in our study corroborated with previous studies from other estuarine regions (Sekiguchi et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Proteobacteria was the most dominant phyla in all the stations irrespective of the sampling period, with only marginal variations in the percentage of occurrence, with Betaproteobacteria, Alphaproteobacteria, and Gammaproteobacteria being the dominant classes. The dominance of Proteobacteria was in concurrence with reports from other tropical estuaries (Bouvier and del Giorgio 2002;Ghosh and Bhadury 2019;Ortmann and Santos 2016;Eswaran and Khandeparker 2019) and also from coastal waters of India (Sachithanandam et al 2020, Parvathi et al 2019. High abundance of Betaproteobacteria and Alphaproteobacteria in our study corroborated with previous studies from other estuarine regions (Sekiguchi et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…This study also reported the absence of anammox bacteria at both locations (Table 5 ). AS metagenome sequence analysis of coastal sediments was reported by Sachithanandam et al ( 2020 ), revealed that microbial communities showed a significant correlation with physicochemical parameters (salinity and dissolved oxygen). Based on functional prediction from this study, most bacterial communities were involved in the biodegradation and bioremediation processes.…”
Section: Coastal and Marine Ecosystemsmentioning
confidence: 90%
“…In the coastal and offshore waters, the phylum Proteobacteria and Firmicutes, predominates and other phylum reported were Bacteroidetes, Actinobacteria, Cyanobacteria, Chloroflexi, and Planctomycetes, with dominating classes of Alphaproteobacteria and Gammaproteobacteria (Kumar et al 2019 ; Mootapally et al 2021 ; Sachithanandam et al 2020 ; Lincy and Manohar 2020 ; Raiyani and Singh 2020 ). This observation was concurrence with reports from the international studies such as Korean coastal waters (Won et al 2017 ) Indian Ocean (Wang et al 2021 ), Ofunato Bay in Iwate Prefecture, Japan (Reza et al 2018 ), Coastal West Antarctic Peninsula (Bowman and Ducklow 2015 ), and Baltic Sea (Ininbergs et al 2015 ).…”
Section: Coastal and Marine Ecosystemsmentioning
confidence: 99%
“…Marine bacteria are diverse and potential as a resource for industrial enzyme applications [1] . Firmicutes are one of the most dominant groups in the Eastern Arabian Sea [2] . Bacillus australimaris B28A was previously isolated from seawater of costal of Thiruvananthapuram, in with deposit 16SrRNA accession number is MT010836.…”
Section: Data Descriptionmentioning
confidence: 99%